MARKETING STRATEGY ANALYSIS CV. NAVALE MITRATAMA USING SWOT METHOD TO IMPROVE COMPETITIVENESS - Monica, Nita Thalia Monica; Panjaitan, Robert Panjaitan; Sihombing , Christina N. (Fundamental Management Journal, 2020)
This Research aims to find out and analyze SWOT strengths, weaknesses, opportunities, threats as CV Navale Mitratama’s marketing strategy using SWOT methods to improve competitiveness. The study is done in may 2020 at CV Navale Mitratama. The hypothesis presented was an analysis of CV Navale Mitratama’s marketing strategy using SWOT methods to improve competitiveness. This research uses a qualitative type of descriptive research. This data is collected through the primary data, and it is analyzed using qualitative descriptive methods of anaanalyzing by using the internal and external swot matrix. The result of swot analysis research have subsequently been a basic refrence to CV Navale Mitratama’s marketing strategies . Keywords: swot analysis, marketing strategies and competitiveness.